Molecular Characterization of Antibiotic Resistance and Genetic Diversity of Klebsiella pneumoniae Strains - Bahareh Arabzadeh; Zeynab Ahmadi; Reza Ranjbar (Canadian Journal of Infectious Diseases and Medical Microbiology)
The aims of this study were the molecular characterization of antibiotic resistance and genotyping of Klebsiella pneumoniae strains isolated from clinical cases in Tehran, Iran. A total of 100 different types of clinical human samples were collected from a major teaching hospital in Tehran, Iran. Bacterial isolates were identified using standard microbiological tests. Antimicrobial susceptibility testing was done according to the latest CLSI guidelines. PCR was used to amplify the gyrA gene in quinolone-resistant isolates and sequencing was performed for the detection of probable mutations between the isolates. The occurrence of plasmid-mediated quinolone resistance genes (qnrA, qnrB, and qnrS) was also investigated by PCR. Finally, genotyping of the strains was performed by PFGE in a standard condition. The susceptibility pattern revealed a high and low level of resistance against meropenem (20%) and trimethoprim (37%), respectively. PCR and sequencing detected mutation in the gyrA gene in 51% of quinolone-resistant K. pneumoniae. According to the susceptibility report, among nalidixic acid-resistant strains, 60.5%, 50%, and 42.9% of isolates contained qnrA, qnrB, and qnrS, respectively. Among ciprofloxacin-resistant strains, qnrA was the most frequent PMQR gene. The PFGE differentiated the strains into 31 different genetic clusters so that the highest number (7/66) was in category A. Our results indicated that the frequency of resistance to various antibiotics particularly trimethoprim, nalidixic acid, and cefoxitin are increasing. The presence of qnr (S and A) genes and point mutation of the gyrA gene were likely to be responsible for the resistance toward nalidixic acid and ciprofloxacin in our strains. Also, the results obtained from genotyping indicated that the K. pneumoniae strains isolated in this study belonged to the diverse clones.